Analysis of Profit Growth of Manufacturing Companies Listed on the Indonesia Stock Exchange (IDX) for 2013-2017 Period - Holly Abas; Freddy S Kawatu; Cecilia Lelly Kewo (AIBPM Publisher, 2020)
This study aims to determine the effect of Liquidity, Leverage, Activity, and Profitability Levels on profit growth in manufacturing companies listed on the Indonesia Stock Exchange in 2013-2017. This research applied causal associative research (causal research). The data used are manufacturing company financial statements from the Indonesia Stock Exchange publications on www.idx.co.id. The data are analysed by conducting quantitative analysis figured with numbers. The results showed that the level of Liquidity measured by a quick ratio (QR) of 0.151, with an error probability of 0.015 implied a positive and significant effect on profit growth. The level of Leverage as measured by Debt to Equity Ratio (DER) of -1.029, with an error probability of 0.005, indicated a negative and significant effect on profit growth. The level of Activity measured by Inventory Turnover (ITO) of 0.288, with error probability of 0.113, suggested a positive and insignificant effect on profit growth. The level of Profitability as measured by Return on Equity (ROE) of 0.569, with error probability of 0.033, implied a positive and significant effect on profit growth, levels of liquidity, leverage, activity, profitability. In addition, as measured by a simultan test (F) of 0.451, with error probability of 0.002, the level of Liquidity, Leverage, Activity, Profitability simultaneously show a significant effect on profit growth.